Evaluation, Financial Statements EVALUASI LAPORAN KEUANGAN BERDASARKAN SAK - EMKM PADA PT. SINAR CAHAYA PAGI - Jaurino Jaurino (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2021)
This study focuses on the application of SAK EMKM in the financial statements of PT. Sinar Cahaya Pagi, which aims to assist companies in making reports based on SAK EMKM and to find out the supporting and inhibiting factors in preparing financial reports based on SAK EMKM. The research method used is descriptive research method with a comparative approach, to determine the preparation of the financial statements of PT. Sinar Cahaya Pagi and compile these financial reports based on SAK EMKM. Researchers will evaluate how the preparation of the financial statements of PT. Morning Light with SAK EMKM. Based on the results of the study it can be concluded that SAK EMKM has not been applied in the preparation of the financial statements of PT. Morning Light rays because the recording does not reflect the actual condition of the company. Supporting factors in the preparation of financial statements at PT. Sinar Cahaya Pagi based on SAK EMKM, namely transactions and expense accounts that do not occur so much every month, can make it easier to make reports based on SAK EMKM, the educational background of a graduate in accounting, and support from the director to implement SAK EMKM. Inhibiting factors are the lack of understanding, lack of awareness of employees to report properly and correctly, and lack of supervision from superiors, namely the director